New Colonialism in an Ecological Guise - Jusmalia Oktaviani; Firdaus Muhamad Iqbal (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2025)
Waste trade from developed to developing countries reflects systemic environmental racism. Wealthy nations turn poorer nations into dumping grounds, creating structural injustice and geography-based discrimination. The concept of ecological colonialism reinforces this, highlighting environmental exploitation in colonized countries. Environmental issues and so-called “green” policies are often used by developed nations to impose dominance over the Global South. This is manifested in the exploitation of natural resources, dependency on debt and foreign loans, technological domination, and waste colonialism. Such practices demonstrate that environmental protection is prioritized only for the powerful, while marginalized communities are sacrificed, thereby reinforcing structural inequality and dependency. This study frames waste trade not as ordinary commerce but as a form of domination over developing countries, particularly in Asia and Africa. Using qualitative methods and secondary data collection, it presents a theoretical framework to explain how waste trade becomes a tool for developed nations to create structural dependency.